Simtuzumab treatment of advanced liver fibrosis in HIV and HCV‐infected adults: results of a 6‐month open‐label safety trial. (6th July 2016) - Meissner, Eric G.; McLaughlin, Mary; Matthews, Lindsay; Gharib, Ahmed M.; Wood, Bradford J.; Levy, Elliot; Sinkus, Ralph; Virtaneva, Kimmo; Sturdevant, Dan; Martens, Craig; Porcella, Stephen F.; Goodman, Zachary D.; et al.
Abstract: Background: Chronic liver injury can result in fibrosis that may progress over years to end‐stage liver disease. The most effective anti‐fibrotic therapy is treatment of the underlying disease, however when not possible, interventions to reverse or slow fibrosis progression are needed. Aim: The aim of this study was to study the safety and tolerability of simtuzumab, a monoclonal antibody directed against lysyl oxidase‐like 2 (LOXL2) enzyme, in subjects with hepatitis C virus (HCV), human immunodeficiency virus (HIV), or HCV‐HIV co‐infection and advanced liver disease. Methods: Eighteen subjects with advanced liver fibrosis received simtuzumab 700 mg intravenously every 2 weeks for 22 weeks. Transjugular liver biopsies were performed during screening and at the end of treatment to measure hepatic venous pressure gradient (HVPG) and to stage fibrosis. Results: Treatment was well‐tolerated with no discontinuations due to adverse events. No significant changes were seen in HVPG or liver biopsy fibrosis score after treatment. Exploratory transcriptional and protein profiling using paired pre‐ and post‐treatment liver biopsy and serum samples suggested up‐regulation of TGF‐β3 and IL‐10 pathways with treatment. Conclusion: In this open‐label, pilot clinical trial, simtuzumab treatment was well‐tolerated in HCV‐ and HIV‐infected subjects with advanced liver disease. Putative modulation of TGF‐β3 and IL‐10 pathways during simtuzumab treatment merits investigation in future trials.